Connexin43 represents an important regulator for Sertoli cell morphology, Sertoli cell nuclear ultrastructure, and Sertoli cell maturation - Sarah Staggenborg; Rüdiger Koch; Kristina Rode; Hanna Hüneke; Louiza Tiedje; Gudrun Wirth; Marion Langeheine; Ines Blume; Kerstin Rohn; Christoph Wrede; Christiane Pfarrer; Ralph Brehm (Scientific Reports, 2022)
Abstract The Sertoli cell (SC)-specific knockout (KO) of connexin43 (Cx43) was shown to be an effector of multiple histological changes in tubular morphology, resulting in germ cell loss through to a Sertoli-cell-only (SCO) phenotype and vacuolated seminiferous tubules containing SC-clusters. Our present study focused on the effects of Cx43 loss on SC ultrastructure. Using serial block-face scanning electron microscopy (SBF-SEM), we could confirm previous results. Ultrastructural analysis of Sertoli cell nuclei (SCN) revealed that these appear in clusters with a phenotype resembling immature/proliferating SCs in KO mice. Surprisingly, SCs of fertile wild type (WT) mice contained SCN with a predominantly smooth surface instead of deep indentations of the nuclear envelope, suggesting that these indentations do not correlate with germ cell support or spermatogenesis. SBF-SEM facilitated the precise examination of clustered SCs. Even if the exact maturation state of mutant SCs remained unclear, our study could detect indications of cellular senescence as well as immaturity, emphasising that Cx43 affects SC maturation. Moreover, Sudan III staining and transmission electron microscopy (TEM) demonstrated an altered lipid metabolism in SCs of Cx43 deficient mice.